2017
DOI: 10.18202/jam23026332.15.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Company Bankruptcy Prediction in Indonesia With Altman Z-Score Model

Abstract: Abstract:Model Altman is one of the models used to predict financial distress. Some of the results of research that conducted in Indonesia showed that Altman model is completely accurate in predicting financial distress but the other found the opposite results. This inconsistency indicates the need to adapt the model by checking whether variables affect Altman model in financial distress companies in Indonesia and the adjustment coefficients Altman to be able to better predict about financial distress. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…Lee et al (2014) findings are supported by Lundholm (1995). Dolejšová (2015) and Matturungan et al (2017) confirmed that the Altman and Springate models had 80% accuracy for predicting a company's financial status. This result was also supported by Syamni et al (2018).…”
Section: Tablementioning
confidence: 62%
See 1 more Smart Citation
“…Lee et al (2014) findings are supported by Lundholm (1995). Dolejšová (2015) and Matturungan et al (2017) confirmed that the Altman and Springate models had 80% accuracy for predicting a company's financial status. This result was also supported by Syamni et al (2018).…”
Section: Tablementioning
confidence: 62%
“…Aaron et al (2017), Husein and Pambekti (2015) stated that it is possible to predict potential bankruptcy using three methods, the Altman Z-score, the Springate model and the Zmijewski model. Matturungan et al (2017) mentioned that the Altman method is the most appropriate bankruptcy predictor for food and beverage companies listed on the IDX. This result is supported by Husein and Pambekti (2015), Karaca and Ercan (2017), Nandhini et al (2012), Oz and Simga-Mugan (2018), Sinarti and Sembiring (2015) and Zhou et al (2015).…”
Section: Tablementioning
confidence: 99%
“…. Altman Z-score has the power to predict one year ahead bankruptcy of manufacturing companies as much as 87.8 percent (includes in good category) in Indonesia (Matturungan, Purwanto, & Irwanto, 2017), 86 percent (includes in great fit category) in Malaysia (Odibi, Basit, & Hassan, 2015), 86.1 percent in Thailand (Meeampol et al, 2014). Altman Z score is used to predict performance of manufacturing companies in Singapore as weIl (Foo, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Lakshan & Wijekoon (2013) examined using 70 bankrupt companies and 70 nonbankrupt companies listed on the Colombo capital market in the period [2002][2003][2004][2005][2006][2007][2008] showing working capital to total assets affected the financial distress of companies both bankrupt and not. Research conducted by Darmawan & Supriyanto (2018), Delavar et al (2015), Caballero et al (2014), and Matturungan et al (2017) also show the results that working capital to total assets affects the company's financial distress.…”
Section: Introductionmentioning
confidence: 88%